Q: What is X and y intercept of -2x plus 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3y+2x = -x+5 y = -x+5/3 So the y intercept is 5/3

x intercept: (1.5, 0) y intercept: (0, 3)

At the x-intercept, y = 0 So, from the equation, 2x + 0 = 12 or x = 6 So the x-intercept is (6,0)

To find the intercept of the line 2x - 3y + 50, we need to set one of the variables to zero. The x-intercept occurs when y is zero, so we can solve for x by setting y=0: 2x - 3(0) + 50 = 0. Simplifying, we get 2x + 50 = 0, which gives x = -25. Therefore, the intercept is (-25, 0).

2x - 3y = 0 y = 2x/3 (at x-intercepts, y = 0) therefore, 2x/3 = 0 x = 0. x = 0 is the x- intercept

Related questions

-4

3y+2x = -x+5 y = -x+5/3 So the y intercept is 5/3

x intercept: (1.5, 0) y intercept: (0, 3)

The x-interceptin is where the graph crosses the y-axis, which is where y equals 0: 0 = 2x + 3 2x = -3 x = -3/2 So the x intercept is as x = -3/2 (and y = 0).

x-intercept: 6; y-intercept: 3

2x + 3y = 12For the y-intercept, x=0:2(0) + 3y = 123y = 12y = 4Therefore, the y-intercept is at y=4, or (0,4)For the x-intercept, y=0:2x + 3(0) = 122x = 12x = 6Therefore, the x-intercept is at x=46, or (6,0)

Set y = 0: So 2x =a ie x = a/2. So the x-intercept is (a/2, 0) Set x = 0: So 3y = a ie y = a/3. So the y intercept is (0, a/3)

The x intercept is where y = 0 y = 2x +5 = 0 2x + 5 = 0 2x = -5 x = -5/2 = -2.5

At the x-intercept, y = 0 So, from the equation, 2x + 0 = 12 or x = 6 So the x-intercept is (6,0)

We should always start with slope-intercept form: 2x + 3y = 24 3y = -2x + 24 y = -2x/3 + 8 Once in this form we see that our y-axis intercept is 8. To find our x-axis intercept, we solve the equation substituting 0 for y: 0 = -2x/3 + 8 -8 = -2x/3 x = (-8)(-3/2) x = 24/12 x = 12

To find the intercept of the line 2x - 3y + 50, we need to set one of the variables to zero. The x-intercept occurs when y is zero, so we can solve for x by setting y=0: 2x - 3(0) + 50 = 0. Simplifying, we get 2x + 50 = 0, which gives x = -25. Therefore, the intercept is (-25, 0).

2x - 3y = 0 y = 2x/3 (at x-intercepts, y = 0) therefore, 2x/3 = 0 x = 0. x = 0 is the x- intercept